2017
DOI: 10.1515/abm-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distraction task on driving performance of experienced taxi drivers

Abstract: Background: Driving performance is influenced by human, vehicular, and environmental factors. Objectives: To investigate the effects of distraction tasks, such as sending a text message (STM) and searching a navigation device (SN), on the driving performance of experienced taxi drivers. Methods: Twelve male taxi drivers (age: 56.3 ± 4.4 y; experience: 28.4 ± 6.4 y) and 14 female taxi drivers (age: 55.5 ± 3.5 y; experience: 19.4 ± 5.0 y) drove in a simulator at a constant speed (90 km/h) for 2 min while maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A recent study reported SCR amplitude increased with cognitive load due to dual-task driving (Ruscio et al, 2017 ). Additional workload experienced due to texting and navigation (Seo et al, 2017 ) and speeding (Kajiwara, 2014 ) while simulated driving was also found to increase EDA.…”
Section: Psychophysiological Measures To Assess Cognitive Statesmentioning
confidence: 92%
“…A recent study reported SCR amplitude increased with cognitive load due to dual-task driving (Ruscio et al, 2017 ). Additional workload experienced due to texting and navigation (Seo et al, 2017 ) and speeding (Kajiwara, 2014 ) while simulated driving was also found to increase EDA.…”
Section: Psychophysiological Measures To Assess Cognitive Statesmentioning
confidence: 92%
“…Performing secondary tasks while Editorial Office of Asian Biomedicine driving can distract attention from driving and increase the possibility of traffic accidents. In this issue of Asian Biomedicine, Seo et al have brought attention to the effects of distracting activities, such as sending a text message or searching navigation, on the driving performance of experienced drivers [7]. They demonstrated a change in the skin conductance level, which is a surrogate measure of the level of activation of the sympathetic nervous system during distraction activities [7].…”
mentioning
confidence: 99%
“…In this issue of Asian Biomedicine, Seo et al have brought attention to the effects of distracting activities, such as sending a text message or searching navigation, on the driving performance of experienced drivers [7]. They demonstrated a change in the skin conductance level, which is a surrogate measure of the level of activation of the sympathetic nervous system during distraction activities [7]. They also demonstrated a relative change in average following distances and speed deviation [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations